When art meets taxonomy: identity of Erythrina laeta (Fabaceae) - Guacchio, Emanuele Del; Cennamo, Paola; Torres, Mario Vázquez; Menale, Bruno (Phytotaxa, 2016)
The unresolved name Erythrina laeta Dehnh. is neotypified by a water-colour kept in the Botanical Garden of Naples (Italy). The Dehnhardt’s name resulted to be a heterotypic synonym of E. americana. The nomenclatural types of the names and their synonyms are discussed, and the names E. enneandra DC. and E. fulgens Loisel. are lectotypified by two pictures.